MEASUREMENTS OF THE COMPLEX PERMITTIVITY OF ACID-DOPED ICE FROM 1 KHZ TO 30 MHZ : NEW DATA SET FOR DEVELOPING ICE RADAR AND DIELECTRIC ANALYSIS OF ICE CORES - マツオカ, ケンイチ; フジタ, シュウジ; マツオカ, タケシ; イシダ, トシヒロ; ホンドウ, タケオ; マエ, シンジ; MATSUOKA, Kenichi; FUJITA, Shuji; MATSUOKA, Takeshi; ISHIDA, Toshihiro; HONDOH, Takeo; MAE, Shinji (National Institute of Polar Research, 1996)
P(論文) We measured the complex permittivity of pure and acid (HCl, HNO_3 and H_2SO_4)-doped ice from 1 kHz to 30 MHz and from -9℃ to -33℃. The complex permittivity of acid-doped ice is assumed to depend linearly on the concentration. The frequency and temperature dependence of the relationship between the complex permittivity and the acid concentration are investigated. The tendency of dielectric dispersion of acid-doped ice is discussed. A simple calculation shows that the reflection coefficient due to acidity change in the HF band in ice sheets increases with decreasing frequency. The effect of permittivity changes and loss tangent changes due to acidity changes to reflection coefficient are quantitatively shown, respectively. As a result, a data set which is essential to develop HF ice radar, and to compare radar echoes and ice core signals is established. departmental bulletin paper